Plant functional type affects nitrogen use efficiency in high-Arctic tundra. (March 2016) - Oulehle, F.; Rowe, E.C.; Myška, O.; Chuman, T.; Evans, C.D.
Abstract: To unravel the potential effects of climate warming on soil N availability in a high Arctic tundra ecosystem we studied temperature effects on soil mineralization, and N uptake from different soil depths (−3, −10 and −30 cm) by tundra plants. Uptake was assessed using 15 N tracer injected directly into mineral soil as 15 NH4 Cl solution to specifically mimic altered N availability from enhanced mineralization. Net N mineralization rates were very low, suggesting that N is strongly limiting in this system. There was no apparent temperature effect (−2 °C, 5 °C, 10 °C) on mineralization, but net nitrification was strongly limited by temperature – under the −2 °C treatment no nitrification occurred. As a consequence of ongoing mineralization and limited nitrification under freezing conditions, mineral NH4 may accumulate during the winter season and be available for plant uptake without risk of loss via NO 3 − leaching immediately after snowmelt. Nitrogen uptake niches were clearly stratified by depth. Graminoids ( Carex misandra and Luzula arctica ) were most effective at taking up N from deep soil horizons, and recovery in graminoid biomass after one year was independent of 15 N injection depth. Recovery of N by the dwarf shrub Salix polaris was significantly higher following shallow application (−3 cm) compared to deeper treatments (−10 and −30 cm). Lichens and mosses also showed a decline in N uptake with application depth, and very little N was recovered by lichens and mosses even from −3 cm, in contrast to the strong uptake that has been observed in mosses when N is applied to the vegetation surface. The ability of graminoids to access nutrients from deeper mineral soil may give them an advantage over mosses and dwarf shrubs in warmer high Arctic tundra in acquiring limited available nutrient resources. Highlights: Limited effect of soil temperature on net N mineralization. Soil freeze limits net N nitrification, thus prevent N leaching during the winter. Plant functional types vary in the soil depth from which they take up N. Nitrogen added above-ground will have different effects to N mineralised within the soil.